Get together, feel together, act together: International personal contact increases identification with humanity and global collective action. (1st October 2018) - Römpke, Anne‐Kristin; Fritsche, Immo; Reese, Gerhard
Abstract: Declining natural resources or climate change are examples of global challenges that characterize our globalized world. A sustainable human cohabitation depends on global intergroup cooperation and joint efforts to solve these crises. Intergroup contact tends to reduce intergroup prejudice and can facilitate such intergroup cooperation. Another line of research indicates that these improved attitudes may reduce the motivation to collective action among members of disadvantaged groups in situations of intergroup conflict, indicating that intergroup contact and collective action are antagonistic processes. In this article, we argue instead that intergroup contact may facilitate collective action intentions against global crises (e.g., climate change or global economic inequalities) that require international cooperation. Specifically, we propose international contact to foster recategorization on the level of all humanity, and in turn intentions of globally responsible actions. We first review evidence of the effects of contact with regard to intergroup cooperation. It is followed by a discussion of the unique nature of collective action concerning a common global challenge. We then integrate both lines of research within the Common Ingroup Identity approach. In two empirical studies ( N 1 = 104, N 2 = 259), we show first evidence that international contact increases identification and solidarity with humanity which then (according to Study 2) is also positively related to intentions of global responsible behavior. Our analysis thus suggests that intergroup contact, beyond the improvement of attitudes, may serve as an effective initiator of social change.